Fundamentals of osteoarthritis: outcome evaluation with patient-reported measures and functional tests. Issue 6 (June 2022) - Davis, A.M.; King, L.K.; Stanaitis, I.; Hawker, G.A.
Summary: Evaluating outcome in osteoarthritis (OA) clinical research and practice requires reliable, valid and responsive patient-reported outcome measures (PROMs) and functional tests that reflect important problems experienced by people with OA. The goal of this work is to provide information to start to guide the reader in selecting measures for people with OA. In this narrative review, we begin by providing an overview of measurement properties that can help clinicians and researchers in making decisions about whether a measure might be appropriate for use in their research or clinical context. We then report evidence supporting the use of measures of pain (e.g., Pain Visual Analogue (VAS), Numeric Pain Rating Scale (NPRS), Intermittent and Constant Osteoarthritis Pain, PROMIS Pain Interference, and, for screening in research, the painDETECT and the Self-report Leeds Assessment of Neuropathic Symptoms and Signs) and fatigue (e.g., PROMIS-Fatigue) at a group level in clinical research. Several multi-dimensional joint-specific measures (e.g., Western Ontario McMaster Universities' Osteoarthritis Outcomes Scale, Knee/Hip Injury and Osteoarthritis Outcome Score, Oxford Hip/Knee Scale) also have evidence for group-level use. Functional tests (e.g., timed walk tests, 30 Second Chair Stand, Timed Up and Go, etc.) have measurement properties supporting their use at the group level in clinical research and at the individual patient level as do the pain VAS and NPRS. Other generic and disease-specific PROMs have been used in or could be used in OA studies but their measurement properties require further evaluation in people with OA.